Implementation of Public Service Supervision Function in Government Agencies by the Ombudsman of The Republic of Indonesia - Mamluatus Sa'adah; Catur Wido Haruni; Esfandiari, Fitria (Indonesia Law Reform Journal, 2024)
Public service is an important part of government administration that directly impacts people's lives. The quality and effectiveness of public services are the most important factors influencing public satisfaction and faith in government. The Ombudsman of the Republic of Indonesia, an autonomous agency governed by Law Number 37 of 2008, regulates the delivery of public services in Indonesia. As a result, the purpose of this study is to discover and investigate the Ombudsman of the Republic of Indonesia's execution of the public service supervisory function in government agencies, as well as the challenges encountered and the efforts taken to overcome them. This study used the sociological juridical research approach. This study used primary data, specifically data obtained directly by researchers through in-depth interviews with the chairman and staff of the Ombudsman of the Republic of Indonesia, as well as secondary data, which included laws, documents related to public service supervision, and Ombudsman reports, to gain a better understanding of the supervisory function's implementation, which was then analyzed descriptively qualitatively. The study's findings shed light on the Ombudsman's implementation of the public service oversight function, including the challenges it faced and the measures made to overcome them. This study also makes recommendations for improving the efficacy of public service monitoring in government entities. This research is expected to help Indonesia create public service oversight rules and practices, allowing government agencies to improve public services to better fulfill the requirements of the population. Abstrak Pelayanan publik merupakan bagian penting dari administrasi pemerintahan yang berdampak langsung pada kehidupan masyarakat. Kualitas dan efektivitas pelayanan publik adalah faktor terpenting yang mempengaruhi kepuasan dan kepercayaan publik terhadap pemerintah. Ombudsman Republik Indonesia, sebuah lembaga otonom yang diatur oleh Undang-Undang Nomor 37 Tahun 2008, mengatur penyelenggaraan pelayanan publik di Indonesia. Oleh karena itu, tujuan penelitian ini adalah untuk menemukan dan menyelidiki pelaksanaan fungsi pengawasan pelayanan publik oleh Ombudsman Republik Indonesia di instansi pemerintah, serta tantangan yang dihadapi dan upaya yang dilakukan untuk mengatasinya. Penelitian ini menggunakan pendekatan penelitian yuridis sosiologis. Penelitian ini menggunakan data primer, khususnya data yang diperoleh langsung oleh peneliti melalui wawancara mendalam dengan ketua dan staf Ombudsman Republik Indonesia, serta data sekunder, yang meliputi undang-undang, dokumen terkait pengawasan pelayanan publik, dan laporan Ombudsman, untuk mendapatkan pemahaman yang lebih baik tentang pelaksanaan fungsi pengawasan, yang kemudian dianalisis secara deskriptif secara kualitatif. Temuan studi ini menjelaskan implementasi fungsi pengawasan layanan publik oleh Ombudsman, termasuk tantangan yang dihadapinya dan langkah-langkah yang dilakukan untuk mengatasinya. Studi ini juga memberikan rekomendasi untuk meningkatkan efektivitas pemantauan pelayanan publik di entitas pemerintah. Penelitian ini diharapkan dapat membantu Indonesia menciptakan aturan dan praktik pengawasan pelayanan publik, memungkinkan lembaga pemerintah untuk meningkatkan pelayanan publik untuk memenuhi kebutuhan penduduk dengan lebih baik.